DETERMINASI NILAI PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Anantyo Herlambang (2017)
This study was conducted to examine the effect of variable Firm Size, Dividend Policy and Managerial Ownership on Firm Value in manufacturing companies in Indonesia Stock Exchange 2012-2015. The population in this study a sample of 68 manufacturing companies listed in Indonesia Stock Exchange 2012-2015 by purposive sampling method. Data obtained from the financial statements of the company which has been in publication. The analysis technique used is multiple linear regression and hypothesis testing. The results showed that (1) firm size (SIZE LN) not significant effect on firm value (TOBINS'Q), (2) dividend policy (DPR) not significant effect on firm value (TOBINS'Q), (3) managerial ownership (MOWN) not significant effect on firm value (TOBINS'Q). Limitations of this study secondary data obtained from the company's financial report shows that there are many companies that share ownership and does not make the payment of dividends by purposive sampling of 133 companies to 17 companies manufacturing in Indonesia Stock Exchange 2012-2015. This study suggests to investors to pay attention to other factors affecting the firm value in making an investment decision.